Evaluation on the antiviral activity of arctigenin against spring viraemia of carp virus - Shen, Yu-Feng; Liu, Lei; Chen, Wei-Chao; Hu, Yang; Zhu, Bin; Wang, Gao-Xue (Aquaculture, 2018)
Spring viraemia of carp virus (SVCV) causes high morality in several economically important cyprinid fishes, but there is no approved therapy up to now. To address the urgent need for therapeutics to combat SVCV infection, we investigated the anti-SVCV activities of 12 natural compounds and 7 common antiviral agents using epithelioma papulosum cyprini (EPC) cells in this study. From the 19 compounds, we identified arctigenin (ARG) has the highest inhibition on SVCV replication, with maximum inhibitory percentage on SVCV>90%. And the 48h half maximal inhibitory concentrations (IC50) of ARG on SVCV glycoprotein and nucleoprotein were 0.29 (0.22–0.39) and 0.35 (0.29–0.41)mg/L respectively. In addition, ARG significantly reduced SVCV-induced apoptosis and recovered SVCV-activated caspase-3/8/9 activity. Further, cellular morphological damage induced by SVCV was blocked by ARG treatment. Mechanistically, ARG did not affect SVCV infectivity. Moreover, ARG could not induce reactive oxygen species (ROS) generation, which plays an antiviral role on SVCV. Interestingly, SVCV-induced autophagy which is necessary for virus replication was inhibited by ARG treatment. These results indicated that the inhibition of ARG on SVCV replication was, at least in part, via blocking SVCV-induced autophagy. Taken together, ARG has the potential to work as an agent for protecting economically important fishes against SVCV. •Anti-SVCV activities of 12 natural compounds and 7 common antiviral agents were investigated.•ARG showed the highest inhibition on SVCV replication.•ARG could inhibit reactive oxygen species generation and apoptosis induced by SVCV.•Autophagy induced by SVCV, which is required for virus replication, was inhibited by ARG treatment.•ARG has the potential to work as an agent for protecting economical fishes against SVCV.